Small molecules as tools to study the chemical epigenetics of lysine acetylation. (August 2018) - Schiedel, Matthias; Conway, Stuart J
Graphical abstract: Abstract : Lysine acetylation has emerged as a key post-translational modification found at many sites throughout the cell. It plays an important role in epigenetic processes, and more generally in the regulation of protein stability and interactions. Acetyl groups are installed by lysine acetyltransferases and removed by lysine deacetylases. Acetylated lysine residues function as binding sites for bromodomains, which are epigenetic reader protein modules that mediate protein–protein interactions. Progress in the development of small molecules that interfere with lysine acetylation has stimulated intensive research activity in diverse therapeutic areas. Some of these compounds are already marketed as drugs or are undergoing clinical trials. Here we review recent progress in the development of small molecules that interfere with lysine acetylation state and acetyl-lysine reading by bromodomains.